A 3D printed low‐profile wideband circularly polarised elliptical integrated lens antenna - Bin Xu; Bing Zhang; Xiao An (IET Microwaves, Antennas & Propagation, 2024)
Abstract The authors presents a low‐profile wideband circularly polarised (CP) millimetre‐wave (mmWave) elliptical integrated lens antenna (ILA) fabricated by dielectric 3D printing technology. The proposed lens is integrated with a dielectric polariser and an air cavity for phase compensation, which can transfer incident waves from linearly polarised (LP) to planar CP waves over a wide bandwidth. Compared to the classic bifocal ILA, the proposed lens has a low profile. The phase compensation is performed by introducing a specifically shaped air cavity, which greatly reduces the length and weight of the lens. The polariser causes the two electric field components Ex and Ey to degenerate with an orthogonal phase difference, which results in the wideband characteristics of the antenna. The polariser, air cavity and lens can be conveniently and precisely fabricated by low‐cost 3D printing technology. Measurements show that the proposed ILA has a wide axial ratio (AR) bandwidth of 21.9–32.6 GHz, while the gain reaches 22.54 dBic with a 38% size reduction and a 60.7% weight reduction. Benefiting from the low profile, high gain, wide bandwidth and low cost, the proposed ILA has great potential to be the candidate antenna for 5G applications and satellite communications.